This town ebook - Leibovich, Mark (2013)
A #1 New York Times bestseller A gripping expose that delves into the heart of Washington D.C., and the intersection of big politics, big money, big media, and big vanity Through the eyes of author Mark Leibovich, we discover how the funeral for a beloved newsman becomes the social event of the year; how political reporters are fetishized for their ability to get their names into the predawn e-mail sent out by the city's most powerful and puzzled-over journalist; how a disgraced Hill aide can overcome ignominy and emerge with a more potent "brand" than many elected members of Congress. And how an administration bent on "changing Washington" can be sucked into the ways of This Town with the same ease with which Tea Party insurgents can, once elected, settle into it like a warm bath. Outrageous, fascinating, and very necessary, This Town is a must-read whether you're inside the highway which encircles DC—or just trying to get there.